Extracellular Polymeric Substances Acting as a Permeable Barrier Hinder the Lateral Transfer of Antibiotic Resistance Genes - Hu, Xiaojie; Kang, Fuxing; Yang, Bing; Zhang, Wei; Qin, Chao; Gao, Yanzheng (Frontiers in Microbiology, 2019)
Antibiotic resistance genes (ARGs) in bacteria are emerging contaminants as their proliferation in the environment poses significant threats to human health. It is well recognized that extracellular polymeric substances (EPS) can protect microorganisms against stress or damage from exogenous contaminants. However, it is not clear whether EPS could affect the lateral transfer of ARGs into bacteria, which is one of major processes for the dissemination of ARGs. This study investigated the lateral transfer of ARGs carried by plasmids (pUC19, pSHG298, and pSHG396) into competent Escherichia coli cells with and without EPS. Transformant numbers and transformation efficiency for E. coli without EPS were up to 29 times of those with EPS at pH 7.0 in an aqueous system. The EPS removal further increased cell permeability in addition to the enhanced cell permeability by Ca2+, which could be responsible for the enhanced lateral transfer of ARGs. The fluorescence quenching experiments showed that EPS could strongly bind to plasmid DNA in the presence of Ca2+ and the binding strength (LogKA = 10.65–15.80 L mol-1) between EPS and plasmids was positively correlated with the enhancement percentage of transformation efficiency resulted from the EPS removal. XPS analyses and model computation further showed that Ca2+ could electrostatically bind with EPS mainly through carboxyl group, hydroxyl group and RC-O-CR in glucoside, thus bridging the plasmid and EPS. As a result, the binding of plasmids with EPS hindered the lateral transfer of plasmid-borne ARGs. This study improved our understanding on the function of EPS in controlling the fate and transport of ARGs on the molecular and cellular scales.